2012
DOI: 10.1021/la303143w
|View full text |Cite
|
Sign up to set email alerts
|

Speciation Analysis of Aqueous Nanoparticulate Diclofenac Complexes by Solid-Phase Microextraction

Abstract: The dynamic sorption of an organic compound by nanoparticles (NPs) is analyzed by solid-phase microextraction (SPME) for the example case of the pharmaceutical diclofenac in dispersions of impermeable (silica, SiO(2)) and permeable (bovine serum albumin, BSA) NPs. It is shown that only the protonated neutral form of diclofenac is accumulated in the solid phase, and hence this species governs the eventual partition equilibrium. On the other hand, the rate of the solid/water partition equilibration is enhanced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 57 publications
1
38
0
Order By: Relevance
“…It may be expected [6,7] that the lability of the complex triclosannanoparticulate species is determined by the rate of diffusive transport of triclosan between the bulk medium and the surface of the spherical nanoparticles. ) is given by [21] :…”
Section: Lability Of the Triclosan-nanoparticle Complexmentioning
confidence: 99%
See 3 more Smart Citations
“…It may be expected [6,7] that the lability of the complex triclosannanoparticulate species is determined by the rate of diffusive transport of triclosan between the bulk medium and the surface of the spherical nanoparticles. ) is given by [21] :…”
Section: Lability Of the Triclosan-nanoparticle Complexmentioning
confidence: 99%
“…Fulfilment of both conditions is not difficult for a sample containing the target analyte only, but in heterogeneous environmental samples containing binding components such as humic acids, nanoparticles and proteins, it becomes a challenge. Association of target molecules with different sample constituents generally leads to lowering of the concentration measured by SPME (if only the free form is accumulated) [1,6,7] and significant changes in the extraction kinetics (for example by labile complexes of the target that facilitate the diffusive transport [8] ). A recent study utilising confocal laser spectroscopy showed, however, that complexing silica nanoparticles do partition into the extracting solid phase, poly(dimethylsiloxane) (PDMS).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-equilibrium speciation techniques, such as various electrochemical methods [4], diffusive gradients in thin film (DGT) [5], and dynamic solid phase microextraction (SPME) [6], provide a measure of the fluxes and reactivities of species [7][8][9]. The pertaining knowledge is operationally formulated in terms of the lability of the complex species, i.e.…”
Section: Introductionmentioning
confidence: 99%